Low HDL Levels as the Most Common Metabolic Syndrome Risk Factor in Heart Failure - Karadag, Makbule Kutlu; Akbulut, Mehmet (Int Heart Journal Assoc, 2009)
Metabolic syndrome (MetS) includes some parameters which are associated with cardiovascular events and risk of developing heart failure (HF). The aim of the present study was to explore the prevalence of metabolic syndrome and individual MetS parameters among heart failure patients. Stable HF patients who had in ejection fraction (EF) <= 35% were included. They were evaluated for MetS and parameters according to the Adult Treatment Panel III (ATP III) of the National Cholesterol Education Program (NCEP). One hundred and nine patients (72 males, 37 females; mean age, 67 +/- 12 years) were included. The most prevalent parameters were low HDL-C (69%) and hypertension (69%) in all participants. No significant change was observed in the prevalence of these parameters due to gender (P > 0.05). Hypertension, increased waist circumference, and hypertriglyceridemia were all significantly more common in women (P < 0.05). The prevalences of hypo-HDL-emia, hyperglycemia, and hypertension did not differ significantly with an advanced age (P > 0.05), whereas hypertriglyceridemia and high waist circumference were significantly decreased in the elderly (P < 0 05). The overall MetS prevalence was 51% and it was significantly higher in women (76% versus 37%, P : 0.003). The prevalence of MetS clearly decreased with age, although the difference was not statistically significant (61% versus 46%, P : 0.57). The mean number of positive MetS parameters also changed significantly with age (3 +/- 1.4 versus 2.5 +/- 1.3, P : 0.046). EF did not change with mean number of MetS parameters (P > 0.05). Hypo-HDL-emia and similarly hypertension were the 2 most common MetS parameters in HF patients. Hypo-HDL-emia and hypertension were the most common parameters observed in all participants and no significant difference was seen due to gender or age. Even though the prevalence of MetS and the mean number of parameters were significantly more common in females and young patients, EF did not change with changes C in these parameters. Based on the results obtained, we conclude that the early diagnosis and treatment of MetS as well as the measurement of individual parameters, especially the most frequent ones, may prevent heart failure or improve its status. (Int Heart J 2009; 50: 571-580)
Keywords: Heart failure; Metabolic syndrome; HDL-cholesterol